Retraction: The development and preliminary validation of a social-emotional skills assessment instrument for Estonian lower secondary school students (vol. 27, iss. 2, pp. 297-314, 2024) - Einpaul, Piret; Leijen, Äli; Baucal, Aleksandar; Psihološka istraživanja, Editorial Board of the journal (Psihološka istraživanja, 2025)
In the article entitled "The development and preliminary validation of a social-emotional skills assessment instrument for Estonian lower secondary schools students", published in No. 2, Vol. 27 of Psihološka istraživanja on pp. 297-314 (https://scindeks-clanci.ceon.rs/data/pdf/0352-7379/2024/0352-73792402297E.pdf), an earlier version of the text was published due to an administrative error in the editing of the manuscript. The authors and editors of Psihološka istraživanja apologise to the readers for this omission. We are pleased to publish the final version of the text under the same title in this issue of Psihološka istraživanja (No. 1, vol. 28, pp. XXX-XXX). (LINK NA CLANAK U .PDF).